ADC Mapping and T2 Mapping of the Lumbar Spine to Assess Disc Degeneration: A Review - Abhijith, S.; Ravichandran, Kayalvizhi (Journal of Health and Allied Sciences NU, 2023)
Early detection of disc degeneration and categorizing them is very important for the treatment plan and better prognosis. We aimed to assess the efficacy of apparent diffusion coefficient (ADC) mapping and T2 mapping in the early detection and grading of the severity of degenerative disc disease. In this review, the articles published until July 2022, from the PubMed database were used. All articles contained information about the application of ADC and T2 mapping in the detection of disc degeneration. A total of 40 articles were included in this review. We assessed each article for the feasibility of both techniques to categorize the degeneration. ADC values of nucleus pulposus (NP) showed a negative correlation with Pfirrmann grades and age. T2 values of NP and annulus fibrosus (AF) are significantly decreased with an increase in Pfirrmann grades. And also, as age increases, T2 values of NP and posterior AF decreased significantly. ADC and T2 mapping techniques are sensitive in the detection and categorization of disc degeneration. It is highly recommended to include quantitative magnetic resonance imaging techniques in routine spine imaging protocol in a patient with complaints of back pain.
Keywords: diffusion; MRI; intervertebral disc degeneration; spinal